2015
DOI: 10.7763/joebm.2015.v3.288
|View full text |Cite
|
Sign up to set email alerts
|

Causality between Financial Deepening and Economic Growth in Nigeria: Evidence from a Bootstrap Rolling Window Approach

Abstract: Abstract-This paper investigates the role of financial development on economic growth in Nigeria. Since a causal link may evolve over time, a bootstrap rolling window approach is used to account for potential time variation in the relationship with annual Nigerian data on money supply as a ratio of nominal GDP and real GDP per capita from 1961-2012. Starting first with a full sample bootstrap Granger causality, the results indicate no causality between the two series. The relevant VAR is unstable for the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(43 reference statements)
1
12
0
1
Order By: Relevance
“…The causal relationship between the financial inclusion and agricultural sector output in Nigeria has more indication for independent causality hypothesis. This is in conformity with the conclusion of Demetriades and Hussein (1996), Obafemi et al (2016) and Aye (2015). Though it does not agree with the a priori expectation but it does solidify the result of Error Correction Model (ECM) which revealed that DR, PLR, ACGSF, DDR and PLSE with P-value of 0.2717, 0.0927, 0.6080, 0.4361 and 0.0565 respectively do not have any significant effect on agricultural sector output in Nigeria within the period of study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The causal relationship between the financial inclusion and agricultural sector output in Nigeria has more indication for independent causality hypothesis. This is in conformity with the conclusion of Demetriades and Hussein (1996), Obafemi et al (2016) and Aye (2015). Though it does not agree with the a priori expectation but it does solidify the result of Error Correction Model (ECM) which revealed that DR, PLR, ACGSF, DDR and PLSE with P-value of 0.2717, 0.0927, 0.6080, 0.4361 and 0.0565 respectively do not have any significant effect on agricultural sector output in Nigeria within the period of study.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The implication therefore is that the rolling window subsample Granger causality test is more suitable to investigate the time-varying Granger causal relationship between DEF and GDP. Following the works of Pesaran and Timmermann (2005) and Aye (2015), the study chose a rolling window with a fixed size of 15. From Figure 1, we observe from the estimated bootstrapped p-values which tests the null hypothesis that GDP does not Granger cause DEF is rejected at a statistical significance of 10% in the 1983-1987,1995-1996 and 2005 sub-sample periods.…”
Section: Resultsmentioning
confidence: 99%
“…Aye [21] investigated the role of financial development on economic growth in Nigeria. Since a causal link may evolve over time, a bootstrap rolling window approach was used to account for potential time variation in the relationship with annual Nigerian data on money supply as a ratio of nominal GDP and real GDP per capita from 1961-2012.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%